Arterial function, apelin and atherosclerotic cardiovascular disease in patients with reumatoid arthritis - Gunter, Sule (My University, 2018)
Rheumatoid arthritis (RA) increases the risk of atherosclerotic cardiovascular disease (CVD) to a similar extent as diabetes. RA is a prototypic high-grade systemic inflammation disease. In RA, systemic inflammation and its related adverse traditional cardiovascular risk factor profiles are each associated with cardiovascular event rates. The mechanisms whereby systemic inflammation enhances CVD risk in RA are currently under investigation. In this regard, impaired arterial function mediates cardiovascular events in non-RA persons. Apelin improves arterial function and reduces atherosclerosis. This thesis comprises a series of investigations that explored the potential role of impaired arterial function and apelin in cardiovascular risk and its stratification amongst patients with RA. Associations were consistently determined in multivariate regression models. RA patients experience arterial stiffness. We firstly assessed the relationships of comprehensively assessed traditional cardiovascular risk factors and RA disease characteristics with measures of arterial function including arterial stiffness as well as wave reflection and pressure pulsatility in 177 patients that met the American College of Rheumatology/European League Against Rheumatism classification RA criteria. Recorded characteristics explained 37% (arterial stiffness) to 71% (reflected wave pressure) of variability in arterial function. RA duration (p=0.04), rheumatoid factor status (p=0.01 to 0.03), leukocyte counts (p=0.02 to 0.05) and total cholesterol concentrations (p=0.00 to 0.03) were associated with increased central systolic pressure (cSP) and/or wave reflection markers. Body mass index (p=0.00 to 0.02) and insulin resistance (p=0.00 to 0.01) were related to reduced wave reflection and peripheral pulse pressure. Tumour necrosis factor-α inhibition (p=0.00) was related to reduced arterial stiffness and tetracycline use (p=0.02) to decreased peripheral pulse pressure (pPP). This study showed that traditional cardiovascular risk factors and RA characteristics are independently associated with measures of arterial function. Secondly, we evaluated the potential impact of impaired arterial function on atherosclerosis in patients with RA. Carotid intima-media thickness (c-IMT) and plaque were determined by ultrasound. In 163 patients with RA, 1 SD increase in reflected wave pressure (Pb) (OR 8 (95%CI)=2.54 (1.41-4.44), p=0.0001), reflection magnitude (Rm) (OR (95%CI)=1.84 (1.17-2.89), p=0.0008), central pulse pressure (cPP) (OR (95%CI)=1.89 (1.12-3.22), p=0.03) and pPP (OR (95%CI)=2.09 (1.23-3.57), p=0.007) were associated with carotid plaque. The association of wave reflection with plaque was independent of arterial stiffness and pressure pulsatility, and was present in both hypertensive and normotensive RA patients. In receiver operator characteristic curve analysis, the optimal cutoff value for reflected wave pressure in predicting plaque presence was 25 mmHg with a sensitivity, specificity, positive predictive value and negative predictive value of 45.2%, 89.3%, 78.6% and 66.2%, respectively. Arterial function was not independently related to c-IMT. We concluded that consideration and therapeutic targeting of wave reflection may improve CVD prevention in RA. Apelin causes vasodilation and reduces blood pressure but these effects are dependent on endothelial integrity. Therefore, in the third investigation, we determined the association of apelin concentrations with measures of arterial function in 170 RA patients. Apelin concentrations were not associated with arterial function in all patients. Inflammation impacted the apelin-arterial function relations (interaction p <0.05). In stratified analysis, apelin levels were associated with decreased cSP (partial r =-0.33, p=0.01), cPP (partial r =-0.26, p=0.04) and forward wave pressure (partial r =-0.33; p=0.01) in patients without but not with joint deformities; apelin concentrations were related to reduced cSP in those with a Disease Activity Score in 28 joints (DAS 28) below but not ≥2.8 (median value) (partial r =-0.24, p=0.05) and in those with an erythrocyte sedimentation rate (ESR) below but not ≥13 mm/h (median value) (partial r=-0.30, p=0.01). Taken together, apelin may improve arterial function in RA but this potential effect may be lost among patients with a large inflammatory burden. Fourthly, we evaluated the potential effects of apelin on ultrasound determined atherosclerosis and markers of plaque stability (matrix metalloproteinase (MMP)-2 and MMP-9) in 235 patients with RA. Apelin concentrations were inversely associated with those of MMP-9 (β (SE) = -0.239 (0.060), p=0.000). Apelin concentration-subclinical CVD relations were influenced by population origin, RA disease activity, ESR and interleukin-6 concentrations (interaction p = 0.001 to 0.04). Accordingly, apelin concentrations were directly associated with those of MMP-2 in white but not 9 black patients (β (SE) = 0.367 (0.146), p=0.01), in those with an ESR below but not ≥12 mm/h (median value) (β (SE) = 0.428 (0.143), p=0.0003), and in those with an interleukin-6 concentration of below but not ≥3.25 pg/ml (median value) (β (SE) = 0.485 (0.288), p=0.04); apelin levels were inversely related to cIMT in patients with RA remission or mild (β (SE) = -0.068 (0.033), p = 0.04) but not moderate or high disease activity (β (SE) = 0.015 (0.112), p = 0.7). This investigation revealed that apelin concentrations are associated with altered plaque stability mediator levels and atherosclerosis in RA. These relationships are partially dependent on population origin and systemic inflammatory status. Taken together, the findings reported in this thesis advance our understanding of the mechanisms by which CVD risk is increased in patients with RA. Evidence is provided that disease characteristics including particularly inflammation and traditional cardiovascular risk factors are strongly associated with measures of arterial function in RA. Impaired arterial function is independently related to atherosclerosis in patients with RA. Impaired arterial function may therefore link cardiovascular risk factor exposure to CVD outcomes in patients with RA. Additionally, apelin may protect against impaired arterial function and atherosclerosis in RA. In this regard, a loss of beneficial apelin effects on the vasculature may contribute to the reported relationship between disease severity and enhanced cardiovascular risk in RA. Apelin holds promise as a therapeutic target in the present context. Our findings further reiterate the need for adequate disease control and CVD risk management in patients with RA.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg for the degree Doctor of Philosophy, 2018
Keywords: Arthritis, Rheumatoid--therapy; Arteriosclerosis